Safety profile of TNF- alpha Inhibitors in pediatric patients: A post-marketing surveillance study based on the FAERS database - Yanmo Yang; Peng Wang; Qin-xuan Li (PLoS ONE, 2025)
This study systematically evaluated the safety profile of tumor necrosis factor-alpha (TNF-α) inhibitors in pediatric patients using data from the U.S. Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) from Q1 2004 to Q3 2024.Through disproportionality analysis of adverse event (AE) reports for infliximab, etanercept, adalimumab, golimumab and certolizumab, we identified 852 significant safety signals spanning 27 system organ classes (SOCs). The most frequently reported SOCs included General Disorders and Administration Site Conditions (12,940 cases), Injury, Poisoning, and Procedural Complications (5,503 cases), and Gastrointestinal Disorders (4,346 cases).Key findings revealed that infection-related AEs and injection-site reactions were the predominant safety concerns. The median onset time of AEs was 235 days (IQR: 46–832 days), with 19.8% of cases occurring within the first month of treatment. Notably, 25.5% of reported AEs required hospitalization, while fatal and life-threatening outcomes accounted for 0.9% and 1.4% of cases, respectively. This comprehensive analysis confirms the multisystemic involvement and prolonged latency of TNF-α inhibitors-associated AEs in pediatric populations. While these agents remain vital for managing chronic inflammatory diseases, the findings advocate for enhanced clinical vigilance. We propose a tiered monitoring protocol prioritizing infection surveillance (e.g., serial inflammatory markers), systematic injection-site evaluations, and longitudinal organ function assessments, particularly during the initial treatment phase, to optimize therapeutic risk-benefit ratios.